ANALISIS KAUSALITAS FERTILITAS DENGAN PERTUMBUHAN EKONOMI DAN KEMISKINAN DI SUMATERA BARAT - Saputra, Robby; Sentosa, Sri Ulfa (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract: This study aims to determine the causal relationship between fertility, economic growth and poverty in West Sumatra. This type of research is descriptive and associative research. The data used are secondary data in the form of panel data from 2010 to 2017. The research methods used are: (1) Vector Auto Regression Analysis, (2) Granger Causality Test. The results showed that (1) There was no causality relationship between fertility and economic growth in West Sumatra, but there was a direct relationship between fertility and economic growth. (2) There is no causality relationship between fertility and poverty in West Sumatra, but there is a direct relationship between poverty and fertility. (3) There is no causal relationship between economic growth and poverty in West Sumatra, but there is a direct relationship between poverty and economic growth.Keywords: Fertility, Economic Growth, Poverty